A STUDY OF RELATIONSHIP BETWEEN DIGITAL LEADERSHIP OF SCHOOL ADMINISTRATORS AND ACADEMIC ADMINISTRATION UNDER PHICHIT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Phanchaiya, Jatupol; Wechayaluck, Nirada (Journal of MCU Nakhondhat, 2025)
The purposes of this study were: 1) To examine the digital leadership of school administrators; 2) To Investigate their academic administration practices; and 3) To analyze the relationship between digital leadership and academic administration among school administrators under the Phichit Primary Educational Service Area Office 1. This study employed a quantitative research design. The sample included 97 institutions, with respondents comprising 97 school administrators selected through purposive sampling and 97 teachers selected using simple random sampling, yielding a total of 194 participants. Questionnaire was used as the research instrument. Data were analyzed using descriptive statistics percentages, means, standard deviations as well as Pearson’s product moment correlation coefficient. The findings indicated that: 1) The overall level of digital leadership among school administrators was high ( = 4.45, S.D. = .41), with the highest mean score in digital citizenship, followed by professional practice, and the lowest in integrated learning skills and innovation; 2) The overall level of academic administration was also high ( = 4.51, S.D. = .41), with the highest mean in the development and use of educational technology, followed by educational supervision, and the lowest in curriculum development; and 3) There was a moderately high positive correlation between digital leadership and academic administration. The strongest correlation was found between digital citizenship and the development and use of educational technology, followed by digital competency and educational technology development, while the weakest correlation was observed between digital vision and educational supervision.